Green Accounting Framework: Analysis of the Influence of Green Supply Chain, Green Culture, and Green Marketing on Sustainability Performance - Yuana Jatu Nilawati; Vivia Gunawan; Kristian Chandra; Arnolt Kristian Pakpahan; Cicely Delfina Harahap (PT. Cendekia Sapta Indonesia, 2026)
Purpose ― This study examines the effects of Green Supply Chain Management (GSCM), Green Organizational Culture (GOC), and Green Marketing (GM) on corporate sustainability performance, and proposes a Green Practice Index (GPI) as an integrated Green Accounting Framework. Methods ― This study employs a quantitative explanatory approach using secondary data from non-cyclical companies listed on the Indonesia Stock Exchange during the 2023–2024 period. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and multiple linear regression to assess both individual and integrated effects of green practices. Findings ― The results indicate that GSCM and GOC have positive and significant effects on sustainability performance, highlighting the importance of operational integration and organizational values. In contrast, GM shows a significant negative effect, suggesting that marketing-based sustainability initiatives may not directly improve performance. Furthermore, the Green Practice Index (GPI) demonstrates a positive and significant influence, confirming that an integrated approach provides stronger explanatory power than partial models. Implication ― The findings suggest that firms should prioritize internal integration of sustainability practices, particularly within supply chain and organizational culture. Regulators are also encouraged to strengthen oversight to enhance the credibility of sustainability practices and reporting. Originality ― This study contributes to the literature by introducing a composite Green Practice Index that integrates multiple dimensions of green practices, offering a more comprehensive framework for measuring sustainability performance.